Analisis Keterbacaan The Missing Colors Sebagai Teks Bacaan Efl Untuk Siswa Sekolah Dasar Berbasis Kajian Flesch-Kincaid - Sitti Fatima Nurlisa Manoppo (-, 2026)
This study analyses the readability of The Missing Colors, a bilingual English-Indonesian picture book, to evaluate its suitability as an EFL reading text for Indonesian elementary school students (Grades IV–VI). Employing a quantitative descriptive design, the Flesch Reading Ease (FRE) formula and the Flesch-Kincaid Grade Level (FKGL) index were applied to an extracted corpus of 314 words, 36 sentences, and 386 syllables (ASL = 8.72; ASW = 1.23). The FRE score was 93.93 (Very Easy) and the FKGL score was 2.33 (Grade 2 equivalent). Within the Indonesian EFL context, the text is linguistically appropriate for upper-primary learners aged 9–12. The study argues that the text's syntactic simplicity is an intentional authorial strategy enabling complex affective themes—bullying, social exclusion, and emotional recovery to be conveyed accessibly to young readers. The Missing Colors is recommended as a pedagogically suitable resource for literature-based EFL instruction and social-emotional learning at the elementary level.